The general features of the scientific and technical information activities - Zujus, Juozas (Knygotyra, 1986)
The state and ways of development of library-bibliographical and scientific information activities, conceptual requirements of scientific communication to the State information system of the USSR are analysed in the article. The organizational structure of the system is discussed, also the methods of information activities and perspectives of its development; the problems of mechanisation and automation of information processes and creation of the network of automated information centres are reviewed. The place and the role of each five levels of information organs in the information system is showed: that of the state information institutes, the central organs of branch information, republican information organs, regional interbranch information centres, and information network of enterprises and organizations, including scientific-technical and special libraries.
Keywords: -